No pain, no gain? Examining the influence of Ibuprofen consumption on muscle hypertrophy - Grgic, J. (Strength and Conditioning Journal, 2023)
This article aims to provide an overview of the effects of ibuprofen ingestion on muscle hypertrophy and determine factors that may moderate its effect. Currently, only 2 studies reported that ibuprofen has a differential effect from placebo on muscle hypertrophy. One study reported that 1,200 mg of ibuprofen augments muscle hypertrophy in older adults. Another study found that the same dose of ibuprofen attenuated muscle hypertrophy in young adults. These contrasting findings are likely explained by the differences in inflammatory levels between the age groups. Older adults generally have higher levels of inflammation, which is why an anti-inflammatory medication might have contributed to muscle hypertrophy. Studies that used lower doses of ibuprofen, such as 400 mg, did not report a negative or positive effect of ibuprofen use. More importantly, the modulating effects of ibuprofen on muscle hypertrophy should be currently considered preliminary because they have not yet been replicated. Meta-analytical data also did not find a significant difference between the effects of placebo and ibuprofen on muscle hypertrophy in middle-aged and older adults. In summary, ibuprofen use may modulate the effects of resistance training on muscle hypertrophy, but more research on the topic is needed before making any conclusive recommendations.